MOVA: uma análise bibliográfica de seus 30 anos de (re)existência - Zacharias, Maria Alice (Universidade Federal de São Carlos, 2022)
The present research has as its object of study the bibliographical research of the Youth and Adult Literacy Movement (MOVA) in the years 1989 to 2019, in order to understand what the academic publications of the national bases about MOVA point out, what its limitations and the elements that have kept the program active for three decades. In addition, we sought to find out if there is an announcement of emancipatory practices and/or policies that can contribute to the development and improvement of popular education and the education of young people, adults and the elderly. adapting to different contexts and, as it has humanistic and popularly based characteristics, subjects bond more easily in relation to formal education, following an active program. For this, bibliographical research was used according to the conception of Salvador (1978) and the communicative methodology (GÓMEZ et al, 2006) for data analysis, based on Paulo Freire's theory of dialogicity (1999) and on the theory of action communication by Jürgen Habermas (1989). The results refer to the collection made in the national bases, specifically the BDTD and CAPES, and indicate a great concentration in the master's research carried out in the State of RS and SP based on different themes such as curriculum, teacher training, pedagogical practices and public policies, but which mostly indicate the lack of legal support in youth and adult literacy, demonstrating the need for effective strategies to really include youth and adults in educational and training processes.
MOVA: a bibliographical analysis of its 30 years of (re)existence
Keywords: MOVA; EJA; Paulo Freire; Pesquisa bibliográfica; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO